Analysis of Safety Sensors on Grain Transportation Equipment at PT. Pundi Kencana - Pratama, Imam Haris; Putra, Ananda Yutho Wibisono (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
The wheat processing industry is one of the vital sectors that involves a complex and sustainable manufacturing process. In carrying out the wheat transfer process, transportation tools equipped with sensors play an important role in ensuring that moving raw materials runs safely and efficiently. In this study, the aim is to understand the types of sensors used in product transportation and the characteristics of each sensor. The method used is a case study method. Milles and Huberman model the qualitative approach. This study uses three types of sensors in the product moving process: proximity sensors, limit switches, and belt monitors. By using these three sensors, product transfer becomes more efficient and safer. Utilizing safety sensors on transportation equipment can minimize errors in the product transfer process and is also safe because it can prevent malfunctions. Applying these three sensors makes it easier for employees to carry out the product transfer process.